PROBLEMS RELATED TO EXPORTS OF MANUFACTURED PRODUCTS FROM INDIA - Madhusudhan A.; D. Krishnamoorthy (ShodhKosh: Journal of Visual and Performing Arts, 2025)
India was challenged with one of the vilest crises early 1990s when the foreign exchange reserve levels fell to such a minimum extent that the residual resources were sufficient to meet only two-week import requirements. This situation led to a sharp deterioration in the country’s balance of payment position. India lost her international credit rating. After a long and hard struggle by the duo Prime Minister Shri P. V. Narasimha Rao and the Finance Minister, Dr. Manmohan Singh, this position has changed very much. Now India’s foreign exchange reserves have gone up to around 638.0 billion (Rs.15,000 crores) which are considered adequately by enough to cover up about six months imports. If the developments during last few years are examined, one can find several measures initiated by the Government of India like import compression, schemes to attract funds from overseas, advancement of financial system, development of advance marketing infrastructure, changes in commercial and economic policies etc. According to the information given by the Press Information Bureau of the Ministry of Commerce and Industry, government of India, India’s total exports during FY 2024-25 (April-March) is estimated at US 820.93 Billion registering a positive growth of 5.50 per cent. Total imports during FY 2024-25 (April-March) were estimated at US 915.19 Billion registering a growth of 6.85 per cent. It is a great achievement in foreign trade and the country has achieved this target with the help of exports especially exports of manufactured products like engineering goods, chemical & allied products, readymade garments, gems & jewellery, leather products etc. The share of manufactured exports in the total exports earnings have been constantly going up. The manufactured products have been playing magnificent role to earn the foreign exchange reserves and they offer better opportunities to the expand export earnings and also to fetch better prices as compared to other non-manufactured and primary products. All efforts should therefore be made to increase the production and productivity of manufactured products, because the export of manufactured products earns more foreign exchange reserve comparatively with no or little fluctuations.